A Liquid Chromatography – Tandem Mass Spectrometry Approach for the Identification of Mebendazole Residue in Pork, Chicken, and Horse - Lee, Ji Sun; Cho, Soo Hee; Lim, Chae Mi; Chang, Moon Ik; Joo, Hyun Jin; Bae, Hojae; Park, Hyun Jin (PLOS ONE, 2017)
A confirmatory and quantitative method of liquid chromatography-tandem mass spectrometry (LC-MS/MS) for the determination of mebendazole and its hydrolyzed and reduced metabolites in pork, chicken, and horse muscles was developed and validated in this study. Anthelmintic compounds were extracted with ethyl acetate after sample mixture was made alkaline followed by liquid chromatographic separation using a reversed phase C18 column. Gradient elution was performed with a mobile phase consisting of water containing 10 mM ammonium formate and methanol. This confirmatory method was validated according to EU requirements. Evaluated validation parameters included specificity, accuracy, precision (repeatability and within-laboratory reproducibility), analytical limits (decision limit and detection limit), and applicability. Most parameters were proved to be conforming to the EU requirements. The decision limit (CCα) and detection capability (CCβ) for all analytes ranged from 15.84 to 17.96 μgkg-1. The limit of detection (LOD) and the limit of quantification (LOQ) for all analytes were 0.07 μgkg-1 and 0.2 μgkg-1, respectively. The developed method was successfully applied to monitoring samples collected from the markets in major cities and proven great potential to be used as a regulatory tool to determine mebendazole residues in animal based foods.